STRATEGI MAHASISWA DALAM MENYELESAIKAN SKRIPSI DI MASA PANDEMI COVID-19 (Suatu Penelitian Pada Program Studi Pendidikan Ekonomi FKIP Universitas Syiah Kuala) - Cut Nurrahmah; Ruaida Ruaida; Amiruddin Amiruddin (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2021)
Students carry out several strategies to be able to complete their thesis during the Covid-19 pandemic. Strategy is a way to achieve the expected goals. The purpose of this study is to find out the strategies undertaken by students in completing theses during the Covid-19 pandemic, to find out the intensity of students in implementing these strategies, and what obstacles are still found in completing the thesis. This study used descriptive qualitative method. Subjects of this study The subjects of this study were 15 students of class 2016 majoring in Economic Education, FKIP Syiah Kuala University who had carried out the thesis trial and who had completed the thesis and students who were waiting for their supervisory lecturer acc for the trial. To answer the problem formulation, interviews were conducted, the focus of the interview was on the strategies carried out by students, the intensity of the students in implementing the strategies and the obstacles faced by students after implementing the strategy of completing a thesis during the Covid-19 pandemic. Interviews using the WhatsApp application, Zoom Meeting, and face to face by applying health protocols. The results of interviews with 15 respondents found that there were several strategies carried out based on the rector's circular, namely implementing health protocols, looking for reference materials through online library applications, Google scholarships and Google books, adjusting research with data collection permits, implementing online and face-to-face guidance. , carry out self-quarantine for 14 days. The intensity of students is that they often look for reference materials but are not scheduled and often communicate with lecturers and thesis guidance is carried out once a week or 2 to 4 times a month. There are obstacles that are still found in completing the thesis, namely accessing library applications is hampered due to system errors, and not all pages of books on Google books can be opened, online guidance with an unstable connection makes the discussion disconnected.Keywords: Student strategy, completing the thesis